Pathogenesis and treatment of idiopathic and rheumatoid arthritis-related interstitial pneumonia. The possible lesson from COVID-19 pneumonia. (2nd August 2020) - Manfredi, A; Luppi, F; Cassone, G; Vacchi, C; Salvarani, C; Sebastiani, M
ABSTRACT: Introduction: Main clinical manifestations of SARS-CoV-2 infection are characterized by fever, dyspnea, and interstitial pneumonia, frequently evolving in acute respiratory distress syndrome (ARDS). Areas covered: Features of coronavirus disease 2019 (COVID-19) presents some common points with interstitial lung disease (ILD) both idiopathic and related to rheumatoid arthritis (RA), typically characterized by a chronic progression over time and possibly complicated by acute exacerbation (AE). The study of common pathogenetic mechanisms, such as the involvement of toll-like receptor 4, could contribute to the knowledge and treatment of idiopathic and RA-ILD. Moreover, hyperinflammation, mainly characterized by increase of effector T-cells and inflammatory cytokines, and activation of coagulation cascade, observed in COVID-19 related ARDS have been already shown in patients with AE of idiopathic and RA-ILD. A literature search was performed in PubMed, Embase, Scopus, and Web of Science, together with a manual search in COVID-resource centers of the main journals. Expert opinion: Despite the uncertainty about pathogenetic aspects about COVID-19- pneumonia, it could be a possible model for other forms of ILD and AE. The great amount of data from studies on COVID-19 could be helpful in proposing safe therapeutic approaches for RA-ILD, in understanding pathogenesis of usual interstitial pneumonia and to develop new therapeutic strategies for AE.